The Implementation of the ISMUBA Curriculum in Al-Islam and Muhammadiyah Studies: A Qualitative Case Study at SMA Muhammadiyah PK Kottabarat Surakarta - fauziyah, safana; Istanto (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to analyze the implementation of the ISMUBA curriculum (Al-Islam, Kemuhammadiyahan, and Arabic Language) in Al-Islam and Kemuhammadiyahan learning at SMA Muhammadiyah Program Khusus Kottabarat Surakarta and its impact on the formation of students' Islamic character. This study employs a qualitative approach with a case study design. Data collection techniques include observation, in-depth interviews, and document analysis. Data validity is tested through triangulation of sources and methods. The research findings indicate that implementing the ISMUBA curriculum has been effective, marked by integrating Islamic and Muhammadiyah values into the learning process. Active and contextual learning methods, such as group discussions, case studies, and role-playing, encourage students' full engagement in cognitive, affective, and psychomotor aspects. However, challenges remain in the limitations of learning media and the need to enhance teachers' competencies. The original contribution of this research lies in its in-depth exploration of the implementation of the ISMUBA curriculum in the context of Muhammadiyah-based secondary schools, which has rarely been comprehensively studied. These findings enrich the body of knowledge in developing an integrative curriculum based on Islamic values and provide practical recommendations for Muhammadiyah educational institutions to improve the curriculum implementation sustainably.